Genetic instability in HSPC subpopulations of umbilical cord blood from patients with childhood acute lymphoblastic leukemia - Katarina Vrobelova; Lukas Jakl; Milan Skorvaga; Pavol Kosik; Matus Durdik; Eva Markova; Jana Jakubikova; Marek Holop; Miroslav Kubes; Martin Cermak; Judita Puskacova; Alexandra Kolenova; et al. (Scientific Reports)
Abstract Preleukemic stem cells (PSC) containing preleukemic fusion genes (PFG) arise prenatally and represent the initial stage of acute lymphoblastic leukemia (ALL) development. Despite widespread efforts, the cell of origin of PFG is still unclear. For the first time, in order to identify the immunophenotype of the PSCs, different subpopulations of hematopoietic stem and progenitor cells (HSPC) of umbilical cord blood (UCB) from ALL pediatric patients and control healthy children were sorted and analyzed for the presence of diagnostically-relevant PFGs by fluorescent in situ hybridization (FISH). Representative FISH results were confirmed by RT-qPCR and validated by sequencing of the products. Not only did we identify likely subpopulations of TEL/AML1+ PSC to be CD34+ CD38+ and CD34+ CD38− cells, but we also found markedly increased instability of often associated with ALL genes in UCB HSPC subpopulations of ALL pediatric patients. Our data show that CD34+ CD38+ as well as CD34+ CD38− cells are prone to genetic instability and most likely represent the target for malignant transformation in the development of ALL. Overall, together with confirming the prenatal origin of PFGs, this study provides further insight into the preleukemic stage of ALL and shows that ALL is a potentially screen able disease.